Analysis of Sharia Financial Literature Factors and Planning Behavior Towards Intention to Using Sharia Banking Products During the Covid-19 Pandemic - Alfarizi, Muhammad (LPPM Universitas Terbuka, 2021)
The pandemic is a real challenge for the business world, including the banking financial services industry. Islamic banks as public intermediary institutions that have funds with those who need funds are required to be able to carry out their activities amid the threat of exposure to COVID-19. Islamic banking has a strategic role in Indonesia's economic development. This study will examine the Islamic financial literacy of the community and the factors of planned behavior in the intention to use Islamic banking products during the Covid-19 pandemic. The Theory of Planned Behavior (TPB) is included in the variables of this study between the variables of financial literacy and intention to use Islamic banking products. This study uses a quantitative method with PLS-Structural Equation Modeling (SEM). The sampling techniques used in this study use convenience sampling techniques. Findings. The results of this study indicate that Islamic financial literacy influences awareness, public attitudes, subjective norms, and perceptions of behavioral control. In addition, the results of the study also show that awareness, subjective norms, and perceptions of behavioral control influence the intention to use Islamic banking products.